Vision, narrative, and wisdom in the Aramaic texts from Qumran essays from the Copenhagen Symposium, 14-15 August, 2017 - Vision, Narrative, and Wisdom in the Aramaic Texts from Qumran 2017 Kopenhagen; Bundvad, Mette 1982-; Siegismund, Kasper; Bach, Melissa Sayyad; Holst, Søren; Høgenhaven, Jesper 1961- ([Erscheinungsort nicht ermittelbar] Brill, 2019)
This volume is a collection of scholarly articles on the Aramaic Dead Sea scrolls, some of the oldest and most fascinating literary compositions among the ancient Jewish manuscripts found in the Qumran caves. Readership: Anyone interested in the Bible, ancient Judaism, the Dead Sea Scrolls, biblical interpretation, and the history of religion
English
Keywords: Dead Sea Scrolls -- Criticism, interpretation, etc -- Congresses; Dead Sea Scrolls -- Relation to the Old Testament -- Congresses; Dead Sea Scrolls; Manuscrits de la Mer Morte - Relation avec l'Ancien Testament - Congrès; Manuscripts, Aramaic -- West Bank -- Qumran Site -- Congresses; Judaism; Manuscrits araméens - Cisjordanie - Qumrān (Site archéologique) - Congrès; RELIGION - Judaism - General; Manuscripts, Aramaic; proceedings (reports); Conference papers and proceedings; Criticism, interpretation, etc; Conference papers and proceedings; Actes de congrès; West Bank - Qumran Site; Konferenzschrift -- 2017 -- Kopenhagen